1975
DOI: 10.1111/j.1476-5381.1975.tb06946.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monoamine Oxidase Inhibition by Clorgyline, Deprenil or Tranylcypromine on 5‐hydroxytryptamine Concentrations in Rat Brain and Hyperactivity Following Subsequent Tryptophan Administration

Abstract: 1 The effect of various doses of tranylcypromine on the degree of inhibition of rat brain monoamine oxidase (MAO) using 5-hydroxytryptamine (5-HT), dopamine and phenylethylamine as substrates has been examined 120 min after injection of the inhibitor. The concentration of brain 5-HT was also examined both after tranylcypromine alone and also when L-tryptophan (100 mg/kg) had been given 30 min after the tranylcypromine. 2 All doses of tranylcypromine greater than 2.5 mg/kg totally inhibited MAO oxidation of 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
77
2
1

Year Published

1976
1976
2002
2002

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 20 publications
16
77
2
1
Order By: Relevance
“…After administration of tranylcypromnine, the non-selective MAO inhibitor, the brain NA level also rises to the concentrations seen after the combination of clorgyline and (-)-deprenyl, with a further increase after L-DOPA. These results are very similar to those obtained for the in vivo deamination of 5-HT and dopamine in the rat brain (Green & Youdim, 1975;Green et al, 1977 The present study thus indicates that while in vitro noradrenaline may be deaminated exclusively by MAO A Suzuki et al, 1979;Kinemuchi et al, 1979), when this enzyme form is fully inhibited in vivo, MAO B can continue to act on noradrenaline, albeit at a slower rate, indicating that the affinity of MAO B as compared to MAO A for NA is much lower. These results are not in agreement with the studies of Neff, Yang & Goridis (1973) and others (Goridis & Neff, 1971;Neff & Fuentes, 1976) who reported that noradrenaline was a specific substrate for MAO A alone in the rat brain.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…After administration of tranylcypromnine, the non-selective MAO inhibitor, the brain NA level also rises to the concentrations seen after the combination of clorgyline and (-)-deprenyl, with a further increase after L-DOPA. These results are very similar to those obtained for the in vivo deamination of 5-HT and dopamine in the rat brain (Green & Youdim, 1975;Green et al, 1977 The present study thus indicates that while in vitro noradrenaline may be deaminated exclusively by MAO A Suzuki et al, 1979;Kinemuchi et al, 1979), when this enzyme form is fully inhibited in vivo, MAO B can continue to act on noradrenaline, albeit at a slower rate, indicating that the affinity of MAO B as compared to MAO A for NA is much lower. These results are not in agreement with the studies of Neff, Yang & Goridis (1973) and others (Goridis & Neff, 1971;Neff & Fuentes, 1976) who reported that noradrenaline was a specific substrate for MAO A alone in the rat brain.…”
Section: Discussionsupporting
confidence: 79%
“…Previously, Green & Youdim (1975), observed that, while in vitro 5-hydroxytryptamine (5-HT) was deaminated exclusively by brain monoamine oxidase (MAO) type A (Johnston, 1968), nevertheless when the latter enzyme form is selectively inhibited in vivo by clorgyline, MAO type B can continue to deaminate the amine. These results have been confirmed by the in vitro studies of Ekstedt (1976) and Fowler & Tipton (1982) using liver and brain mitochondrial preparations respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since the inhibitory effects on uptake of (-)-deprenyl are only apparent at doses far above those that cause complete inhibition of MAO type B (1.0 mg/kg in the rat, see Green & Youdim, 1975), such an action does not apparently play a role in the non-potentiation of tyramine responses at selective MAO-B inhibitory clinical doses of (-)-deprenyl. In addition, since selective inhibition of MAO-B by AGN 1135 also did not result in potentiation of tyramine pressor responses, it may be that complete inhibition of MAO-B is not accompanied by potentiation of indirectly acting amines.…”
Section: Determination Ofmonoamine Oxidase Activitymentioning
confidence: 99%
“…(-)-Deprenyl has been shown to possess amphetamine-like actions on rat locomotor activity (Green & Youdim, 1975) and cat cardiovascular system (Simpson, 1978a) in higher doses than those that selectively inhibit MAO type B. Deprenyl is metabolized to amphetamine and methamphetamine in man (Reynolds, Elsworth, Blau, Sandler, Lees & Stem, 1978), although it is not clear whether deprenyl itself or its metabolites are responsible for this effect. However, AGN 1135 does not possess such intrinsic sympathomimetic activity (Finberg et al, 1979).…”
Section: Determination Ofmonoamine Oxidase Activitymentioning
confidence: 99%
See 1 more Smart Citation